TINGKAT KEPUASAN PENGGUNA JASA DI BANDARA SULTAN SYARIF KASIM II PEKANBARU - Zuriyen, Aisyah; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Customer service is one of the units in Sultan Syarif Kasim II Airport, Pekanbaru. Customer service serves as a more frontline which is a frontline work unit that occupies a strategic position and is in direct contact with customers to provide services and information at the airport. The purpose of this study was to determine the effect of customer service quality on the level of service user satisfaction at Sultan Syarif Kasim II Airport in Pekanbaru. The theory used in this research is the stimulus-response theory.This research uses quantitative research methods, with data collection techniques, namely through the distribution of questionnaires directly to service users with a total sample of 96 respondens, which is determined through an accidental sampling technique. Data analysis techniques in this study using simple linear regression analysis techniques. For processing the questionnaire test data is performed using version 16 of the Windows Product and Service Solution (SPSS) Statistics program.Based on the results of simple linear regression in this study, the regression coefficient value is Y = 2.009 + 0.323 X with a significance level of 0.00 and smaller than α = 0.05. While based on the determination test, the results obtained were 66.1%. This means that there is a strong influence between the quality of customer service on the level of service user satisfaction at Sultan Syarif Kasim II Airport in Pekanbaru.